Friday the 13th [videorecording (DVD)] - Nispel, Marcus, 1964-; Padalecki, Jared, 1982-; Panabaker, Danielle; Yoo, Aaron, 1979-; Righetti, Amanda, 1983-; Van Winkle, Travis (New Line Home Entertainment ; Distributed by Warner Home Video, 2009)
A carload of teenagers head for a weekend of fun at a lakeside cabin. Meanwhile, Clay and Jenna pursue a lead in the search for his missing sister, against the advice of police and cautions from the locals. The lakeside cabin happens to be part of the boarded up Camp Crystal Lake. There, they soon encounter Jason Voorhees and all of his deadly intentions.